Gender studies in development research: A neocolonial agenda? - Dennis Avilés-Irahola; Eva Shamiran Youkhana (University of Bonn, Center for Development Research (ZEF), 2024)
The systematic study of power asymmetries and inequalities between women and men and nonbinary genders, have long been overlooked in development research. Within the complex framework of SDGs that, on the one hand aim at improving the quality of human life but, on the other hand, cement the global centrality of economic growth aligned to the capitalist economic model, we critically reflect on our own experience as female scholars in development studies and cooperation. We argue that gender studies in development research need not only to frame their critical views within decolonial theories, but also to reflect on its practices. We discuss this affirmation along three areas of reflection: the reinforcement of 'internal colonialism'; the need to acknowledge and make visible women's and indigenous voices from the south; and our own decolonial position in our day-today practices within our academic spaces along language, recognition, and caring. We underlie that decoloniality can operate under 'patriarchal' modes, even if contradicting its principle of humans and non-humans as equally valuable. We also argue that a critical engagement with naturalized gender relations, arguably the most pronounced form of a modern linear social reality based on binary oppositions, is a prerequisite for decolonizing scientific practices. Critical and reflexive gender studies can serve as a gateway to critical and reflexive development studies because of its potential to deconstruct discourses of 'legitimacy' (e.g., science vs. traditional knowledge); wealth (e.g., economy vs. social and healthy relations); and education (reproduction of knowledge vs. recognition and co-production of knowledges). We conclude by affirming that gender studies in development research have the potential to be instrumental to the colonial as well as to the decolonial projects, depending on the extent of the conventional or pluralistic / critical views (re)presented in its theory and practice.
Keywords: 330; gender studies; decoloniality; development; education